Strategic Leadership and its Relationship to Administrative Creativity among School Principals from the Point of View of the Administrative Body in Public Education Schools in Jeddah (The International Journal of Educational Sciences and Arts, 2023)
The study aimed to shed light on the reality of the practice of strategic leadership and administrative creativity among school principals from the point of view of the administrative body in general education schools, the descriptive approached applied. A questionnaire consisting of (37) items distributed to the study sample of (365) employees. The results showed that the practice of strategic leadership and administrative creativity in general education schools came with a high degree of approval. The study indicated that there are statistically significant differences between the responses of the study individuals on the axis of the practice of school principals in general education schools in Jeddah for the levels of administrative creativity in different years of experience, and it was shown through the mean ranks These differences are in favor of the study individuals who have more than 10 years of experience (expert), and the study recommended the necessity of involving school principals of the administrative body in formulating its strategic vision and allocating financial resources for the development of human capital and spreading the culture of ethical practices among members of the administrative body.
Keywords: Strategic Leadership; Administrative Creativity; Administrative Body